Durability of Concrete Structures with Sugar Cane Bagasse Ash. (5th October 2020) - Berenguer, R.; Lima, N.; Valdés, A. C.; Medeiros, M. H. F.; Lima, N. B. D.; Delgado, J. M. P. Q.; Silva, F. A. N.; Azevedo, A. C.; Guimarães, A. S.; Rangel, B.
Abstract : The environmental impact of cement production increased significantly in the previous years. For each ton of cement produced, approximately a ton of carbon dioxide is emitted in decarbonation (50%), clinker furnace combustion (40%), raw materials transport (5%), and electricity (5%). Green strategies have been advanced to reduce it, adding natural or waste materials to substitute components or reinforce the mortar, like fibers or ashes. Sugar cane bagasse ash is a by-product generated from sugar boilers and alcohol factories with capacity to be used in concrete production. Composed mainly of silica, it can be used as mortar and concrete mineral admixture, providing great economic and environmental advantages, particularly in regions with sugar culture and industrial transformation like Brazil. In this research, a study of partial substitution of Portland cement by sugar cane bagasse (SCB) is analyzed, in order to reduce clinker in concrete volume, responsible for high emission of CO2 to the atmosphere. An experimental campaign with cementitious pastes was carried out to evaluate the durability properties' changes due to SCB ash use. Samples containing 15% of sugarcane bagasse ash unveiled good results in terms of durability, indicating that concrete structure with sugar cane ash research is a new and important scientific topic to be highlighted.